Efficacy and safety of antiangiogenic agents or chemotherapy plus EGFR‐TKIs in advanced non‐small cell lung cancer: A systematic review and network meta‐analysis - Jiali Dai; Xinyin Liu; Jun Li; Tianyu Qu; Yanan Cui; Shidai Jin; Erbao Zhang; Renhua Guo (Thoracic Cancer, 2023)
Abstract Background The combination of antiangiogenic agents with epidermal growth factor receptor inhibitors (EGFR‐TKIs) and chemotherapy with EGFR‐TKIs are the most common combination treatment options in epidermal growth factor receptor (EGFR) positive non‐small cell lung cancer (NSCLC). This network meta‐analysis was performed to evaluate the differences between them. Methods We searched the PubMed, EMBASE and the Cochrane Controlled Trials Register up to August 2022. The primary outcomes were progression‐free survival (PFS) and objective response rate (ORR). The secondary endpoints were overall survival (OS), disease control rate (DCR) and adverse events (AEs). The data of hazard ratio (HR) or risk ratio (RR) with their corresponding 95% confidence intervals (CIs) were extracted in the studies. A network meta‐analysis (NMA) was used to indirectly compare the efficacy and safety of antiangiogenic agents plus EGFR‐TKIs and chemotherapy plus EGFR‐TKIs. Results Pooled data of included studies were demonstrated that chemotherapy plus EGFR‐TKIs had a benefit in ORR compared to antiangiogenic agents plus EGFR‐TKIs in patients with EGFR mutated NSCLC (RR = 1.1, 95% CI: 1.0–1.2). However, there were no significant differences in PFS, OS and DCR between in the two group (PFS: HR = 1.0, 95% CI: 0.74–1.6; OS: HR = 0.78, 95% CI: 0.45–1.5; DCR: RR = 1.0, 95% CI: 0.94–1.1). The common treatment‐related AEs in the two groups were relatively manageable. Conclusion Based on the efficacy and safety, the combination of chemotherapy with EGFR‐TKIs is considered the best combination treatment options in advanced NSCLC with EGFR mutation.